2018
DOI: 10.1016/j.molp.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Medicago AP2-Domain Transcription Factor WRI5a Is a Master Regulator of Lipid Biosynthesis and Transfer during Mycorrhizal Symbiosis

Abstract: Most land plants have evolved a mutualistic symbiosis with arbuscular mycorrhiza (AM) fungi that improve nutrient acquisition from the soil. In return, up to 20% of host plant photosynthate is transferred to the mycorrhizal fungus in the form of lipids and sugar. Nutrient exchange must be regulated by both partners in order to maintain a reliable symbiotic relationship. However, the mechanisms underlying the regulation of lipid transfer from the plant to the AM fungus remain elusive. Here, we show that the Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(139 citation statements)
references
References 83 publications
5
125
1
1
Order By: Relevance
“…The asterisks indicate significant differences (P , 0.05). (Bravo et al, 2017;Jiang et al, 2017Jiang et al, , 2018Keymer et al, 2017;Luginbuehl et al, 2017). The assay of fatty acid contents in the mycorrhizal roots of wild-type and slhak10 mutant plants showed no significant difference under both the K + supply conditions (Supplemental Fig.…”
Section: Loss-of-function Mutation Of Slhak10 Decreases Mycorrhizal Kmentioning
confidence: 97%
“…The asterisks indicate significant differences (P , 0.05). (Bravo et al, 2017;Jiang et al, 2017Jiang et al, , 2018Keymer et al, 2017;Luginbuehl et al, 2017). The assay of fatty acid contents in the mycorrhizal roots of wild-type and slhak10 mutant plants showed no significant difference under both the K + supply conditions (Supplemental Fig.…”
Section: Loss-of-function Mutation Of Slhak10 Decreases Mycorrhizal Kmentioning
confidence: 97%
“…The RAM1 transcription factor has been identified as an early regulator of the mycorrhiza-specific reprogramming, activating on the one hand genes involved in the transfer of FAs to the fungus [121] and the AM-specific phosphate transporter PT4 on the other [122]. Following different strategies to screen for transcription factors that could bind the promoters of mycorrhiza-inducible genes, two very recent researches identified elements acting downstream RAM1, namely LjCBX1 in Lotus japonicus [123] and MtWRI5a in Medicago truncatula [124]. LjCBX1 binds the conserved cis-regulatory motif "CTTC" enriched in mycorrhiza-regulated genes as well as an AW-box motif present in the promoters of glycolysis and fatty acid biosynthesis genes.…”
Section: Does the Plant Reward The Fungus Only With Sugars?mentioning
confidence: 99%
“…Accordingly, the authors showed that LjCBX1 can activate the transcription of FA metabolic genes as well as of the L. japonicus PT4 [123]. The M. truncatula MtWRI5a transcription factor has also been shown to bind the AW-box motif present in the promoter of the fatty acid ABC transporter STR, as well as the phosphate transporter MtPT4, enhancing their expression [124]. On the contrary, hairy roots of M. truncatula wri5a mutants showed an impaired arbuscule formation [124].…”
Section: Does the Plant Reward The Fungus Only With Sugars?mentioning
confidence: 99%
“…The RAM2 gene encodes a glycero‐3‐phosphate acyl transferase (Wang et al ., ) required for the synthesis of 16:0 β‐monoacylglycerols (β‐MAG) (Bravo et al ., ; Jiang et al ., ; Keymer et al ., ; Luginbuehl et al ., ). AP2 transcription factors CBX1 and WRI5a co‐regulate a divergent set of genes underlying mycorrhizal phosphate uptake and lipid biosynthesis (Jiang et al ., ; Xue et al ., ). β‐MAGs are subsequently exported to the fungus probably via half‐ABC transporters STR to maintain the symbiotic relationship (Bravo et al ., ; Jiang et al ., ; Keymer et al ., ; Luginbuehl et al ., ).…”
Section: Introductionmentioning
confidence: 99%